Biophysical analysis of sialic acid recognition by the complement regulator Factor H. (27th July 2018) - Schmidt, Christoph Q; Hipgrave Ederveen, Agnes L; Harder, Markus J; Wuhrer, Manfred; Stehle, Thilo; Blaum, Bärbel S
Abstract: Complement factor H (FH), an elongated and substantially glycosylated 20-domain protein, is a soluble regulator of the complement alternative pathway (AP). It contains several glycan binding sites which mediate recognition of α2-3-linked sialic acid (FH domain 20) and glycosaminoglycans (domains 6–8 and 19–20). FH also binds the complement C3-activation product C3b, a powerful opsonin and focal point for the formation of C3-convertases of the AP feedback loop. In freely circulating FH the C3b binding site in domains 19–20 is occluded, a phenomenon that is not fully understood and could be mediated by an intramolecular interaction between FH's intrinsic sialylated glycosylation and its own sialic acid binding site. In order to assess this possibility, we characterized FH's sialylation with respect to glycosidic linkage type and searched for further potential, not yet characterized sialic acid binding sites in FH and its seven-domain spanning splice variant and fellow complement regulator FH like-1 (FHL-1). We also probed FH binding to the sialic acid variant Neu5Gc which is not expressed in humans but on heterologous erythrocytes that restrict the human AP and in FH transgenic mice. We find that FH contains mostly α2-6-linked sialic acid, making an intramolecular interaction with its α2-3-sialic acid specific binding site and an associated self-lock mechanism unlikely, substantiate that there is only a single sialic acid binding site in FH and none in FHL-1, and demonstrate direct binding of FH to the nonhuman sialic acid Neu5Gc, supporting the use of FH transgenic mouse models for studies of complement-related diseases.